EVALUATION OF THE KNOWLEDGE LEVEL OF DENTAL POSTOPERATIVE SENSITIVITY WITHIN DENTAL PRACTITIONERS - Tărăboanță-Gamen Andra Claudia; Pancu Galina; Toma Vasilica; Tărăboanță Ionuț; Gianina Iovan; Irina Nica; Sorin Andrian (Romanian Dental Association for Education, 2023)
The aim of the present study was to assess by using a questionnaire, the knowledge and understanding level of dental postoperative sensitivity through dental practitioners. A number of 431 dental practitioners coming from rural or urban practices, in private or public environment, with a bachelor's degree or with postgraduate studies received this specifically developed questionnaire. The questionnaire consisted of a series of socio-demographic questions, followed by 14 questions related to postoperative sensitivity. The questionnaire contained 7 single-choice and 7 multiple-choice questions. For the statistical analysis of the obtained results Pearson Chi-square and Independent sample t-test were used. For all 14 questions, the correct answers were indicated by the majority of respondents, regardless of the training level or the environment of origin. Both postgraduate and bachelor's degree dental practitioners had a similar level of knowledge regarding the etiology, symptomatology and therapeutic management of postoperative dental sensitivity. The knowledge level about dental postoperative sensitivity does not differ between dental practitioners in the public and private sectors.